Pentingnya Pendidikan Jasmani dalam Meningkatkan Kesehatan di SDN 141 Lokajaya - Diniah, Salma Zakiyah Nuri; Saripusin, Cantika Nisrina Taj Jauhara; Putri, Gayasal Agisni; Salsyabella, Ratna Cahya; Khotimah , Raihani Nurul; Gumilar, Dinda Amelia; Mufidah, Siti Rahma; Mulyana, Agus (Indo-MathEdu Intellectuals Journal, 2024)
Physical Education, Sports, and Health (PJOK) has an important role in basic education, not only in improving physical fitness, but also in teaching values such as discipline, responsibility, and cooperation. The main objective of this study is to present a thorough understanding of the important role of physical education in efforts to improve overall public health. This study uses a qualitative approach with interviews and literature analysis to present a comprehensive understanding of the role of PJOK in improving health. Data analysis is carried out qualitatively with stages, namely data reduction, data presentation, and conclusion drawn. The findings suggest that PJOK is not just about physical exercise, but also about building a deep understanding of a healthy lifestyle, with the hope of creating a physically and mentally healthy generation